2020
DOI: 10.1111/1365-2435.13665
|View full text |Cite
|
Sign up to set email alerts
|

The response of the soil bacterial community and function to forest succession caused by forest disease

Abstract: 1. Forest succession is a key driver of plant communities and understanding succession is central to forest restoration. Currently, the information on the response of the microbial community to the forest succession process, however, is limited. In the present study, we investigated the dynamics of the soil bacterial community in three forest types undergoing succession caused by pine wilt disease, representing the initial pine forest, gradual mixed pine and broadleaved forest, and eventual broadleaved forest,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 85 publications
(103 reference statements)
9
32
0
Order By: Relevance
“…Forest restoration strategies varying from active restoration where anthropogenic interventions influence the successional track of recovery, to passive, such as natural forest recovery have been frequently applied after external disturbances (Stanturf et al, 2014). Enhancing knowledge of forest succession and its relationship with the recovery of ecosystem functions is therefore central to forest managers for climate change mitigation and adaptation (Qu et al, 2020;Satdichanh et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Forest restoration strategies varying from active restoration where anthropogenic interventions influence the successional track of recovery, to passive, such as natural forest recovery have been frequently applied after external disturbances (Stanturf et al, 2014). Enhancing knowledge of forest succession and its relationship with the recovery of ecosystem functions is therefore central to forest managers for climate change mitigation and adaptation (Qu et al, 2020;Satdichanh et al, 2018).…”
mentioning
confidence: 99%
“…It has been shown that ectomycorrhizal fungi community was significantly associated with forest succession stages (10-40, 41-80 and >80 years) in Chinese subtropical forests (Gao et al, 2015;Wu et al, 2012). A previous study found that the diversity and richness of bacterial community significantly increased following the succession stages (Qu et al, 2020). However, quantifying individual functions could prohibit the weighing of tradeoffs between ecosystem functions, and provide a biased perception for restoration success (Allan et al, 2015;Garland et al, 2020).…”
mentioning
confidence: 99%
“…The composition, structure, diversity, and interspecies relationship of plant communities changes over time following forests disturbance as a result of both above and underground interactions [ 6 , 7 ]. Plant composition and community structure can affect small-scale environmental changes in forests.…”
Section: Introductionmentioning
confidence: 99%
“…As secondary stands develop, the increase in vegetation biomass could enhance belowground carbon allocation and subsequently soil organism activity (Francini et al, 2018;Morrien et al, 2017). Accordingly, a recent study reported that the microbial biomass carbon, diversity and richness of bacterial community signi cantly increased following the succession stages (Qu et al 2020). Secondly, forest secondary succession can alter soil properties and competition of resources within a soil nematode community (Cesarz et al, 2013;Eisenhauer et al, 2013;Valladares et al, 2012).…”
Section: Introductionmentioning
confidence: 99%